Iterative regularization method of 3D scattering geometry reconstruction - Emets, Volodymyr; Rogowski, Jan (Видавництво Львівської політехніки, 2011)
The problem of the shape reconstruction of a scatterer from the scattered field measured outside under the illumination of an incident plane wave is considered. Theoretically, the inversion algorithm is derived using integral equation formulations together with the Newton-Kantorovich iterative regularization technique. Numerical results show that the good reconstruction is obtained with the only one wave number of the incident wave. The effects of noise on the imaging reconstruction were also investigated.